Microencapsulation of L-carvone and hexyl salicylate in carnauba wax, candelilla wax and beeswax by melt dispersion method - Qun Huang; Zhibing Zhang (Polymer Testing)
Wax microspheres encapsulating flavour or fragrance oil (L-carvone, Hexyl salicylate) prepared via melt dispersion was investigated. This study highlights the influence of different waxes as well as variable oil loadings on the fundamental properties of the resulting microparticles. The mechanical characterisation of individual wax microspheres by a micromanipulation technique is firstly reported here and the values of Young's modulus of wax microspheres were determined by fitting the experimental force versus displacement with the Hertz model. The relation between the payload and Young's modulus of wax microsphere was also explored in this study.